La thérapeutique par le travail contraint à la colonie agricole pénitentiaire des Prés-Neufs (20e siècle) - Mikhaël Moreau; Cristina Ferreira (Swiss Journal of Sociocultural Anthropology, 2020)
Adopting a socio-historical approach, this article aims to draw attention to the continuities and discontinuities that can be observed in the penal treatment of people categorized as “psychopathic delinquents”. The problem posed by their internment in appropriate areas remained a subject of debate throughout the 20th century in Switzerland and was never really resolved. In the Canton of Vaud, one penal farm colony was used for about 50 years to punish and re-educate these individuals through labor. An in-depth examination of the archives allows us to immerse ourselves in the socio-economic life of this institution, to which the inmates contributed fully. After many years of use as a place of correction and assistance, Prés-Neufs became a remand prison in 1983. Thirty years later, plans to create a medico-social establishment on the site were abandoned in favour of Curabilis, a Geneva prison-hospital more in line with the renewed emphasis on security prevailing at the time.